The Influence of Leadership Style of Principal on Kurikulum Tingkat Satuan Pendidikan (KTSP) Implementation at SMP Negeri 06 Pekalongan - NURHAYATI AMANAH (Jurusan tarbiyah- Pendidikan Agama Islam - STAIN Pekalongan, 2009)
The Background this research is about leadership style of principal on Kurikulum Tingkat Satuan Pendidikan (KTSP). This research proposed three statements of the problems as follow is does the leadership style of the principal influence on the KTSP implementation at SMP Negeri 06 Pekalongan, what extent dose the leadership style of the principal influence on the KTSP implementation at the school, and what are the factors of the leadership style of the principal influence on the KTSP implementation at the school. This research used field research as variety of research is qualitative and quantitative approach. From this research result that principal of SMP N 06 Pekalongan mostly shows democratic as his leadership style, There indicated that leadership style of principal influences on KTSP implementation at SMP N 06 Pekalongan. In showing democratic as principal leadership style, he was influenced bya some factors among them are useful shool human resources, family education, formal education background, personality and training for leadership.